A knowledge, attitude and practice study on hand hygiene and antibiotic susceptibility pattern in isolates of pathogens from hands in school children - Harika, V.; Mekala, Swarajya Lakshmi; Amatullah, Fatima; Tipparthi, Sandeep Kumar; Sugunakar Reddy, K. (International Journal Of Community Medicine And Public Health, 2020)
Background: Estimates in India indicate that gastrointestinal infections and respiratory infections are the most common childhood killer diseases. Infectious germs on hands are the commonest way that children spread infections. Present study mainly focused on creating awareness (by practical demonstration) about importance of hand hygiene in school children, which is one of the simplest, low cost and most advisable form of the infection prevention and transmission. Methods: In a school of semi-rural setting, 300 swabs before and after hand wash (with a liquid soap) were collected randomly from dominant hands of 150 students of age group 5-13 years and then transported to laboratory for further processing. Results: Hands of 96.7% students were found to harbor bacteria before handwash which included Micrococcus (60.6%), CONS (6.6%), Neisseria spp. (31.3%), Bacillus spp. (26%), Diphtheroids (9.3%), and potential pathogens like Staphylococcus aureus (16.6%), Klebsiella spp. (2.6%), Escherichia coli (2%). Data indicates that hands of female students are more contaminated than male. There is evidence of 58% reduction in the bacterial flora after hand wash. Conclusions: It has been clearly demonstrated by an orientation programme to all students with results that the initial step in chain of infection can be controlled by proper hand wash technique to prevent communicable diseases and reduce the use of antibiotics.